An improved time-marching formulation based on an explicit time integration method for dynamic analysis of non-viscous damping systems. (15th May 2023) - Liu, Tianhao; Wang, Pan; Wen, Weibin
Abstract: An improved time-marching formulation based on an explicit method [1] is proposed for non-viscous damping systems. In this method, an improved integral approximation scheme is developed to improve the convolution solution accuracy and is applicable to any causal kernel function. The mathematical derivation and calculation procedure based on the explicit method are formulated for non-viscous damping systems. For comparison, a composite explicit method proposed by Noh and Bathe is also extended for non-viscous damping systems. The proposed explicit method shows more desirable stability and accuracy properties than other competitive explicit methods. Numerical simulations of some representative examples demonstrate the proposed time-marching procedure is efficient for dynamic analysis of non-viscous damped systems.